2019
DOI: 10.1111/jen.12685
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and larvicidal activity of indole derivatives against Aedes aegypti (Diptera: Culicidae)

Abstract: In light of the challenges to control Aedes aegypti and the critical role that it plays as arbovirus vector, it is imperative to adopt strategies that provide fast, efficient and environmentally safe control of the insect population. In the present study, we synthesized six indole derivatives (C1‐C6) and examined their larvicidal activity and persistence against Ae. aegypti larvae, as well as their toxicity towards Raw 264.7 macrophages, Vero cells, Chlorella vulgaris BR017, Scenedesmus obliquus BR003, Caenorh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
(96 reference statements)
0
10
0
Order By: Relevance
“…23 Synthetic compounds based on natural molecules with low or no toxicity to non-target organisms can be an efficient alternative to control larvae growth and the mosquito proliferation. [23][24][25][26][27] Chalcones are precursors of several flavonoids in higher plants that exhibit a wide spectrum of biological activities, which are attributed to their single ⊍,⊎-unsaturated ketone nucleus. 28 Chalcones and their derivatives have received considerable attention due to their antitumor, 29 antiviral, [30][31][32] antibacterial, 33 antifungal, 34 antimalarial, 35 antioxidant, 29 anti-inflammatory, 29,36 and antitubercular activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Synthetic compounds based on natural molecules with low or no toxicity to non-target organisms can be an efficient alternative to control larvae growth and the mosquito proliferation. [23][24][25][26][27] Chalcones are precursors of several flavonoids in higher plants that exhibit a wide spectrum of biological activities, which are attributed to their single ⊍,⊎-unsaturated ketone nucleus. 28 Chalcones and their derivatives have received considerable attention due to their antitumor, 29 antiviral, [30][31][32] antibacterial, 33 antifungal, 34 antimalarial, 35 antioxidant, 29 anti-inflammatory, 29,36 and antitubercular activity.…”
Section: Introductionmentioning
confidence: 99%
“…40 The presence of substituent groups in the chemical structure of synthetic larvicidal molecules such as fluorine, chlorine, bromine, nitro and methoxy can improve their activity because these groups modify the physicochemical properties of the molecule such as molecular size, ability to donate and receive hydrogen bonds, ionization state, lipophilicity and water solubility. 27,41 Considering the increasing demand for efficient chemical control agents with low or no toxicity to humans and the environment, in this work we synthesized substituted chalcones and determined their activity against Ae. aegypti larvae and their toxicity towards four non-target organisms: the microalgae Chlorella vulgaris and Scenedesmus obliquus, the ciliated protozoan Tetrahymena pyriformis, and the insect Galleria mellonella.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesized compounds' mortality rate correlates with the recent study reported on the larvicidal activities for halogenated indole derivatives, where chloro and bromo substituents showed improved larvicidal activity. [ 9 ] The other five compounds, 4a (TSINH), 4b (TSINCH 3 ), 4e (TSINO 2 ), 4f (TSINNO 2 ), and 4g (TSINOH), displayed no larvae mortality even after 48 h.…”
Section: Resultsmentioning
confidence: 99%
“…The compounds’ environmental toxicity was estimated from the growth rate of the algae Chlorella vulgaris BR017 and the viability of the protozoan Tetrahymena pyriformis . The toxicity to non-target organisms was determined in Caenorhabditis elegans N2 and Galleria mellonella 9 .…”
mentioning
confidence: 99%
“…aegypti larvae population with low environmental toxicity, such as 6-bromo-2,3,4,9-tetrahydro-1H-carbazole with LC 50/24h = 1.5 mg/L (5.88 μM) 9 . Although the presence of chlorine or bromine groups in the aromatic ring usually improves the larvicidal activity of indole derivatives 9 , the addition of chlorine groups to (PhSe) 2 to produce (p-ClPhSe) 2 considerably reduced larvicidal activity ( Table 1 ). The LC 50 value of (PhSe) 2 and its analogs in mice range from 278 to 381 mg/kg 11 .…”
mentioning
confidence: 99%